Kinematic analysis of the super-extended H I disk of the nearby spiral galaxy M 83 - Eibensteiner, Cosima; Bigiel, F.; Leroy, A. K.; Koch, E. W.; Rosolowsky, E.; Schinnerer, E.; Sardone, A.; Meidt, S.; Blok, W. J. G. de; Thilker, D.; Pisano, D. J.; Ott, J.; et al. (Astronomy and astrophysics, 2023)
We present new HI observations of the nearby massive spiral galaxy M 83 taken with the JVLA at 21″ angular resolution (≈500 pc) of an extended (∼1.5 deg2) ten-point mosaic combined with GBT single-dish data. We study the super-extended HI disk of M 83 (∼50 kpc in radius), in particular disk kinematics, rotation, and the turbulent nature of the atomic interstellar medium. We define distinct regions in the outer disk (rgal> central optical disk), including a ring, a southern area, a southern arm and a northern arm. We examine HI gas surface density, velocity dispersion, and noncircular motions in the outskirts, which we compare to the inner optical disk. We find an increase of velocity dispersion (σv) toward the pronounced HI ring, indicative of more turbulent HI gas. Additionally, we report over a large galactocentric radius range (until rgal ∼ 50 kpc) where σv is slightly larger than thermal component (i.e., > 8 km s−1). We find that a higher star-formation rate (as traced by far UV emission) is not necessarily always associated with a higher HI velocity dispersion, suggesting that radial transport could be a dominant driver for the enhanced velocity dispersion. Furthermore, we find a possible branch that connects the extended HI disk to the dwarf irregular galaxy UGCA 365 and that deviates from the general direction of the northern arm. Lastly, we compare mass flow rate profiles (based on 2D and 3D tilted ring models) and find evidence for outflowing gas at rgal ∼ 2 kpc, inflowing gas at rgal ∼ 5.5 kpc, and outflowing gas at rgal ∼ 14 kpc. We caution that mass flow rates are highly sensitive to the assumed kinematic disk parameters, in particular to inclination.
Online veröffentlicht: 29. Juni 2023
Gesehen am 20.09.2023